PENGAWASAN PEMERINTAH DAN MASYARAKAT DALAM KETERSEDIAAN PRASARANA, SARANA, DAN UTILITAS UMUM PERUMAHAN KOTA KUDUS (STUDI KASUS PERUMAHAN BUMI RENDENG BARU) - Muchamad Syaifudin .; Purwoko . .; Lusia Astrika . (Journal of Politic and Government Studies, 2017)
“Government and Community Supervision In Availability Infrastructure, Infrastructure and Public Utilities in the Holy City Housing (housing case studies Rendeng New Earth)